SOIL MOISTURE MEASUREMENT BY SOIL IMPEDANCE MEASURING METER : LABORATORY CALIBRATION AND FIELD EVALUATION (Biological Sciences - PJSIR, 2002)
Soil impedance measuring meter  is relatively  a  new  device  and  utilises the  principle  of measuring  the dielectric constant of the soil, and hence water content by soil electrical impedance method at 100 MHz. The probe is supplied with a general calibration by the manufacturer and very little has been published on the materials-specific calibration.  Hence, the output  (mV) of the probe was calibrated versus volumetric water content  (8) of silty clay  loam  soils, loamy  very  fine sand  soil  and chalky material. For 8v